Total Synthesis of Chaetoquadrins H and I - Kim, U Bin; Dalebrook, Andrew F.; Furkert, Daniel P.; Brimble, Margaret A. (Synlett, 2013)
The first total syntheses of the chromone-containing natural products chaetoquadrins H and I are reported, using an aldol reaction and an acid-catalyzed deprotection/cyclization/elimination sequence. Chaetoquadrin H was isolated from the ascomycete Chaetomium quadrangulatum and exhibits potent mouse liver monoamine oxidase (MAO) inhibitory activity. Chaetoquadrin I was not isolated in sufficient quantity to enable biological evaluation. The synthesis of the title compounds provides a useful starting point for a medicinal chemistry program focused on chaetoquadrin natural products.
Keywords: monoamine oxidase inhibitors; natural products; spiroketal compounds; aldol reaction